2013
DOI: 10.1259/bjr.20120417
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical implications of incorporating relative biological effectiveness into radiobiological equivalence relationships

Abstract: Objective: Earlier radiobiological equivalence relationships as derived for low-linear energy transfer (LET) radiations are revisited in the light of newer radiobiological models that incorporate an allowance for relative biological effectiveness (RBE).Methods: Linear-quadratic (LQ) radiobiological equations for calculating biologically effective dose at both low-and high-LET radiations are used to derive new conditions of equivalence between a variety of radiation delivery techniques. The theoretical implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…There have been concerns that RBE may be under‐ or overestimated for certain tumors or organs at risk (see Section 4.B.). Theoretical studies have addressed the issue of RBE variations in patients and have analyzed the potential impact of RBE on fractionation in proton therapy . In general, RBE effects will be more prominent in tumors involving low α / β tissues, which makes prostate, breast, sarcoma, and certain brain tumors sites to be cautious with.…”
Section: Assessment Of Clinical Impact When Revising Current Practicementioning
confidence: 99%
See 1 more Smart Citation
“…There have been concerns that RBE may be under‐ or overestimated for certain tumors or organs at risk (see Section 4.B.). Theoretical studies have addressed the issue of RBE variations in patients and have analyzed the potential impact of RBE on fractionation in proton therapy . In general, RBE effects will be more prominent in tumors involving low α / β tissues, which makes prostate, breast, sarcoma, and certain brain tumors sites to be cautious with.…”
Section: Assessment Of Clinical Impact When Revising Current Practicementioning
confidence: 99%
“…There is a need to understand whether or not differences in plans optimized using (LET d times dose) vs (RBE times dose) for relevant molecular or cellular endpoint are large enough to be clinically relevant when viewed against the uncertainties and gaps in our understanding of the underlying clinical endpoint and patient‐specific biology. An increasing number of proton centers are treating patients with proton beam scanning, and it has been shown that variations in RBE might be greater in scanned beams relative to passive scattered beams . IMPT delivered with scanning pencil beams holds the greatest therapeutic potential and will be employed at the majority of new proton centers. Recent theoretical studies have addressed the issue of RBE spatial variations in patients and have analyzed the impact of fractionation on RBE in proton therapy . There is thus increased interest in understanding the clinical relevance of RBE spatial variations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it implies that hypofractionated regimens will result in lower RBE values [57]. Several theoretical studies have addressed the issue of RBE spatial variations in patients [5759] and have analyzed the impact of RBE on fractionation [10, 60, 61]. …”
Section: Rbe Variations In Patientsmentioning
confidence: 99%
“…Fractionation schemes are often compared with dose equivalence calculations that are typically based upon the LQ model (Holloway and Dale 2013). In addition to BED-and LQ-based calculations of dose equivalence, tumor growth models can be incorporated into optimization algorithms that explicitly model changes in tumor volume.…”
Section: Spatial Dose and Fractionation Optimizationmentioning
confidence: 99%